Surrounding rock control technology of gob-side entry retaining in inclined longwall face with large mining height - ZHAO Zhiyan (Meikuang Anquan, 2022)
The mining technology of gob-side entry retaining is widely adopted by China’s coal mining enterprises because of its high economic significance. However, gob-side entry retaining also has some problems, such as long service time, many times of mining influence, and difficult surrounding rock support. In order to explore the key technology of surrounding rock control of gob side entry retaining in 3304 working face, this paper studies the influence of roadway side filling parameters on surrounding rock control of gob side entry retaining by using research methods such as theoretical analysis, numerical simulation and field measurement, and proposed the bolt asymmetric support scheme of gob side entry-retaining through the “three high and one low” bolt support design concept, through the comparison of numerical simulation test and field practice test, it is concluded that the reasonable parameters of roadway side support body and the asymmetric support scheme of anchor bolt have obvious effect on the control of surrounding rock of gob-side entry retaining roadway.